História e proposições políticas e educacionais do sindicato dos profissionais do magistério da rede municipal de São Luís – MA [SINDEDUCAÇÃO] - (1972 - 1992) - Sousa, Vanessa Pereira Amorim de (2023)
The objective of the research was to analyze the history and educational policy propositions of the Union of teaching professionals in the municipal network of São Luís [SINDEDUCAÇÃO], between the years 1972 and 1992, within the framework of a historical periodization that encompassed three distinct moments, but amalgamated and interspersed, namely: the duration of the civil-military dictatorship, the democratic transition and the duration of democracy in Brazil. From the point of view of its theoretical and methodological foundation, the choice of some assumptions that constituted the core of Marxist and Marxian production proved to be more adequate in the development of the present study, since they are authors that make it possible to critically interpret some aspects of the history of the associativism and unionism of workers in education and contemporary educational policies. The qualitative study, based on a wide bibliographical review, on diverse primary sources, such as semi-structured interviews, testimonials from teachers who worked in the union movement and taught in public schools, expanded with the location and analysis of photographs , newspapers, pamphlets, congressional theses and other documents that could collaborate with the general construct of the present study proposal concerned with the preservation of the teaching union memory in the field of the history of Brazilian education. This is because it seems to be significant to try to understand the social reality taking into account its contradictions and antagonisms, its moments of continuities and perspectives of ruptures, valuing the dimension of movement and totality that is found in the very essence of social life. The trajectory of SINDEDUCAÇÃO represents an important moment in the history of education, its experiences and actions required the need to forge and consolidate mechanisms for dialogue between those who aimed to achieve guarantees for the exercise of the teaching profession. Despite the offensives of the capitalist system to the union movement and the fragmentation tactics of the unions to attenuate its strength, they remain imperious in the defense of the establishment of dignified conditions of life and work, assuming responsibilities in the affirmation of freedom and democracy and, in the case of teacher unionism, not only seeking to defend the corporate claims of teachers, but, above all, fighting in defense of public education, free of charge, secular and of socially referenced quality as an inalienable right to exercise Brazilian citizenship.